HUBUNGAN POLA ASUH DEMOKRATIS ORANGTUA DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR - Rosada, Ulfa Danni (STKIP Muhammadiyah Pringsewu, 2019)
The purpose of this study is (1) to find out the relationship between parenting democratic parenting with learning achievement.(2) Knowing the relationship between emotional intelligence and learning achievement.(3) Knowing the relationship between parental democratic parenting and emotional intelligence on learning achievement. The approach used in this study is to use a quantitative approach. The results of this study indicate that:(1) The magnitude of the effect of parenting on learning achievement is 13.7%, (2) The amount of influence of emotional intelligence on learning achievement is 16.4%, (3) The amount of influence of parenting and emotional intelligence on achievement learning by 30.1%.